Consumer ethnocentrism among government servants in Kota Bharu towards buying automobile / Hatinah Abu Bakar ... [et. al] - Abu Bakar, Hatinah; Abdullah, Fatihah Norazami; Wan Husin, Wan Zakiyatussariroh; Yusoff, Zulkarnain; Salleh, Muhammad Shukri (2011)
This study attempts to identify consumer ethnocentrism among government servants in Kota Bharu, Kelantan when buying automobile. The objectives of this study are to identify the level of ethnocentrism among the samples and investigate whether products, prices, dealers, promotions and personal factors have an impact on consumer ethnocentrism in buying automobiles and to assess personal relationship with level of ethnocentrism. The research tool used was in the form of a questionnaire. Based on the responses from respondents, it can be concluded that the level of ethnocentrism among respondents is low. This study revealed that factors influencing consumer ethnocentrism among government servants in Kota Bharu, Kelantan, were products, prices and promotions. To test the relationship between personal and ethnocentrism, Pearson-Chi square was used and the analysis revealed a significant relationship between age and level of education with ethnocentrism in choosing automobiles.